Simplified three-dimensional finite element hot-spotting modelling of a pin-mounted vented brake disc: an investigation of hot-spotting determinants. (June 2018) - Tang, Jinghan; Bryant, David; Qi, Hongsheng; Whiteside, Ben; Babenko, Max
Hot spotting is a thermal localisation phenomenon in which multiple hot regions form on a brake disc surface during high-energy and/or high-speed braking events. As an undesired problem, hot spots can result in high-order brake judder, an audible droning noise and thermal cracking. This paper presents a finite element model for hot-spot modelling which introduces the classical axisymmetric assumptions to the brake pad in three dimensions by scaling the material properties combined with a subroutine to simulate the heat generation instead of modelling the rotation of the brake pad. The results from the initial feasibility models showed significant improvement in the computing efficiency with acceptable accuracy when compared with a traditional finite element model without such simplifications. This method was then applied to three-dimensional simulations of hot spotting on a realistic ventilated brake disc–pad pair, and the results showed good correlation with the experiments. In order to improve the understanding of the hot-spotting mechanism, parametric studies were performed including the effects of a solid-disc geometry and a ventilated-disc geometry, the rotational speed and energy, the pins, the disc run-out and the brake pad length. Based on the analysis of the results, it was identified that the vents and the pins affected the hot-spot distribution. The speed was shown to be more important in the hot-spot generation time and the hot-spot distribution than either the pressure or the total energy input was. The brake disc run-out was shown to affect the magnitude of both the hot-spot temperature and the hot-spot height because of the non-linear relationship between the local deformation, the contact pressure and the heat generation. Finally, increasing the brake pad length generated fewer hot spots, but the temperature of each hot spot increased.